Analysis of Corporate Liquidity Between Cash Flow Ratios and Traditional Ratios (A Survey study on listed Telecommunication companies in the Damascus Stock Exchange ( - قريص عصام; عبد الله اوبان (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This study was aimed at analyzing the liquidity of Telecommunication companies listed on the Damascus Securities Market using cash flow ratios compared to traditional liquidity assessment ratios. The study community may be Telecommunication companies listed on the Damascus Securities Market. Annual financial reports published on the Syrian Securities and Markets Authority website were relied upon during the period (2011-2021) The spss statistical program was used to test the study hypotheses where the sampling method was used using T tests. The study found statistically significant differences between the ratio of trading compared to the ratio of cash coverage and statistically significant differences between the ratio of rapid liquidity compared to the proportion of critical cash requirements and there are no statistically significant differences between critical cash requirements and cash, The cash flow ratios of cash coverage and critical needs ratio have given clearer indications of lower liquidity levels for Telecommunication companies listed on the Damascus securities market compared with traditional ratios of trading ratio and rapid liquidity ratio.